2022
DOI: 10.3390/agronomy12071676
|View full text |Cite
|
Sign up to set email alerts
|

A Metal Chaperone Gene Regulates Rice Growth and Seed Development by Manganese Acquisition and Homeostasis

Abstract: Manganese (Mn) is a mineral element essential for plant growth and development. In agronomy reality, Mn deficiency or overload in crops disturbs metal homeostasis, photosynthesis, and many other biological processes. Mining genetic resources linking Mn acquisition and homeostasis is vitally important to help understand plant adaptation to Mn stress and breeding genetically improved crops for sustainable agriculture. Metallic chaperone (metallochaperone) is a class of family proteins playing an essential role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Deletion of PMR1 in the pmr1 mutant results in a Mn-hypersensitive phenotype with severely blocked cellular growth and an overaccumulation of Mn ions [ 24 ]. This model is widely used for testing Mn transport, detoxification, and accumulation [ 7 , 25 , 26 ]. Our studies showed that under excessive Mn supply conditions, the growth of mutant cells carrying the null gene ( pmr1 + pYES2) was significantly inhibited compared to that of the wild-type (BY4741 + pYES2) yeast ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Deletion of PMR1 in the pmr1 mutant results in a Mn-hypersensitive phenotype with severely blocked cellular growth and an overaccumulation of Mn ions [ 24 ]. This model is widely used for testing Mn transport, detoxification, and accumulation [ 7 , 25 , 26 ]. Our studies showed that under excessive Mn supply conditions, the growth of mutant cells carrying the null gene ( pmr1 + pYES2) was significantly inhibited compared to that of the wild-type (BY4741 + pYES2) yeast ( Figure 5 A).…”
Section: Resultsmentioning
confidence: 99%
“…Local meteorological data recorded no abnormal rainfall, temperature, pest, or disease occurrences, etc. When the rice was totally ripened, all of the tissues and organs of the mature plants were separately harvested [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations